Clinical significance of gastrointestinal patency evaluation by using patency capsule in Crohn’s disease - Yoshimura, Toru (Nagoya J Med Sci, 2018)
Capsule endoscopy (CE) enables noninvasive visualization of the small bowel in Crohn’s disease (CD), but should not be conducted in patients with bowel obstruction. Patency capsule (PC) can be ingested before conducting the CE examination to ensure patency of the gastrointestinal (GI) tract. This study aimed to evaluate the clinical significance of GI patency which the PC demonstrated. A retrospective review of the medical records was conducted with 99 consecutive patients with CD who underwent PC and CE at Nagoya University Hospital from January 2010 to May 2015. By using the Cox proportional hazards model, the association between the GI patency evaluated using the PC and the outcome in terms of the rate of patients who needed admission or surgery during the 2-year follow-up was examined. Of all 99 patients who ingested the PC, 84 (84.8%) were diagnosed as not having bowel obstruction, and therefore were eligible for CE (P group). Of the 15 patients in whom bowel obstruction was suspected (NP group), 12 patients underwent either the balloon-assisted endoscopy (n=10) or enteroclysis (n=2), and 11 were confirmed to have small bowel stricture. Non-admission rates of the P and NP groups during the 2-year observation period were 74/84 (88.0%) and 8/15 (53.3%), respectively (P<0.001). Non-operation rates of the P and NP groups during the 2-year observation period were 80/84 (95.2%) and 9/15 (60.0%), respectively (P<0.001). In conclusion, GI patency as diagnosed using the PC was associated with a significantly lower incidence of admission or surgical intervention.